ILMU DALAM PERSPEKTIF AL-QUR'AN - Retna Dwi Estuningtyas (Institut Agama Islam Negeri (IAIN) Keiri, 2018)
Islam is a religion that teaches its people to always learn. Islam is also a religion that positions science in a noble position. As a sign of the primacy of science in Islam is the nature of science is one of the obligatory properties of Allah SWT. Therefore, all prophets and messengers are sent to teach knowledge to the people they are developing. Science is an important knowledge that people need to answer all the problems of life. By having knowledge, the prosperous world life as well as the happier hereafter will be realized. That's what science is for. Speaking of knowledge, in the Qur'an scattered the word science and all kinds of derivatives. Man, according to the Qur'an has the potential to gain knowledge and develop it with the permission of Allah. Therefore, scattered verses that commanded humans to take various ways to make that happen. Over and over again the Qur'an shows how high the position of the knowledgeable. According to the Qur'anic view - as the first revelation implies - science consists of two kinds. First, science acquired without human effort, is called 'ilm ladunni, as informed among others by the Qur'an. With science then all problems will be solved. With knowledge people will be able to behave better, people will be able to tolerate with others despite different principles.